2010
DOI: 10.1128/jcm.00715-10
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Beijing Lineage Favors the Spread of Multidrug-Resistant Tuberculosis in the Republic of Georgia

Abstract: High rates and transmission of multidrug-resistant (MDR) tuberculosis (TB) have been associated with theMycobacterium tuberculosis complex (MTBC) Beijing lineage, pointing to the importance of pathogen genetic factors for the modulation of infection outcome and epidemiology. We present here an in-depth analysis of the population structure of MTBC strains from the Republic of Georgia, a high-incidence setting at the Black Sea Coast. Phylogenetic lineages were identified based on 24-locus MIRU-VNTR (for mycobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
71
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 36 publications
(54 reference statements)
7
71
2
Order By: Relevance
“…The addition of spoligotyping did not influence the discriminatory power of either of the two other methods but was rather useful for supporting phylogenetic classifications predicted by MIRU-VNTR typing, as previously suggested (1,12). Importantly, all clusters with a confirmed recent transmission link were detected by both MIRU-VNTR and IS6110 RFLP typing.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The addition of spoligotyping did not influence the discriminatory power of either of the two other methods but was rather useful for supporting phylogenetic classifications predicted by MIRU-VNTR typing, as previously suggested (1,12). Importantly, all clusters with a confirmed recent transmission link were detected by both MIRU-VNTR and IS6110 RFLP typing.…”
Section: Discussionmentioning
confidence: 54%
“…The IS6110 fingerprints, spoligotyping patterns, and MIRU-VNTR typing results of the M. tuberculosis complex isolates were analyzed by the BioNumerics program (Windows XP, version 6.5; Applied Maths, Kortrijk, Belgium) as described previously (12,17). The IS6110 patterns were digitized and analyzed for similarity by using the Dice coefficient and a bandmatching tolerance of 1.2%.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the genotyping analysis revealed four lineages (Beijing, LAM, Haarlem and Ural) already reported in the FSU [17][18][19], although the Beijing family was more frequent (68%) in our study. Of interest, the combination of MIRU-VNTR and antibiotic resistance genotypes and phenotypes suggested that almost all strains defined as clustered by MIRU-VNTR were in fact distinct.…”
Section: Discussionmentioning
confidence: 59%
“…Some of the spoligotype families (also called spoligofamilies) are preferentially distributed in particular geographic regions, indicating that they are either spreading locally or better adapted to certain human populations (5-7). Importantly, some spoligofamilies have been associated with outbreaks and multidrug resistance, the Beijing (and Beijing-like) spoligofamily being the best-known example (8)(9)(10)(11). Although predominant in far-east Asia, the Beijing spoligofamily is much less frequently found in the Americas, Europe, and Africa, where LAM, Haarlem, T, and S families predominate (5).…”
mentioning
confidence: 99%